On the Nature and Structure of Self‐Interest, Morality and Practical Reasoning. (22nd April 2016) - Temkin, Larry S.
Abstract: This article is divided into two main sections. In section 1, I highlight some of the most significant results of Parfit's discussion of self‐defeating theories in Part I of Reasons and Persons . I then argue, against Parfit, that, depending on the nature of the good, the structure of consequentialist, or agent‐neutral, theories does not preclude the possibility that such theories may be (seriously) self‐defeating. In section 2, I discuss Parfit's ingenious argument against the self‐interest theory, to the effect that as a "hybrid" theory, which is "partial" with respect to people but "neutral" with respect to time, the self‐interest theory occupies a dangerous middle ground that is open to attack from two sides: on one side, by a "pure" theory that is partial with respect to both people and times, and on the other side, by a "pure" theory that is neutral with respect to both people and times. I then raise doubts, prompted by the form of Parfit's argument, as to whether there is a general requirement that we treat people, places and times the same, except, perhaps, in cases involving special relations. Specifically, I suggest that there may be reason to treat space differently than time, and that there are compelling reasons to treat persons differently than time.